Genomic Characterization of a Uropathogenic Escherichia coli ST405 Isolate Harboring blaCTX-M-15-Encoding IncFIA-FIB Plasmid, blaCTX-M-24-Encoding IncI1 Plasmid, and Phage-Like Plasmid - Yao, Mianzhi; Zhu, Qianhui; Zou, Jin; Shenkutie, Abebe Mekuria; Hu, Songnian; Qu, Jiuxin; He, Zilong; Leung, Polly H. M. (Frontiers in Microbiology, 2022)
Escherichia coli sequence type 405 is an emerging antibiotic-resistant clonal group associated with the global dissemination of extended-spectrum β-lactamase-producing E. coli. In this study, we report the genome assembly and characterization of a uropathogenic E. coli ST405 strain, SZESBLEC201, based on long and short reads obtained from the Nanopore and Illumina sequencing platforms, respectively. Whole-genome sequencing revealed that SZESBLEC201 harbors a 5,020,403 bp chromosome and three plasmids, namely, pSZESBLEC201-1, pSZESBLEC201-2, and pSZESBLEC201-3. pSZESBLEC201-1 (111,621 bp) belongs to the IncFIA-FIB type and harbors blaCTX-M-15. However, this plasmid does not harbor conjugative transfer-associated genes, rendering pSZESBLEC201-1 unable to be conjugatively transferred. pSZESBLEC201-2 (95,138 bp) is a phage-like plasmid that shows a strong genome synteny with Escherichia phage P1 but with the absence of mobile genetic elements and some regulatory genes. pSZESBLEC201-3 (92,865 bp) belongs to the IncI1 type and carries blaCTX-M-24. In contrast to pSZESBLEC201-1, pSZESBLEC201-3 retains its full active conjugation machinery and can be transferred via conjugation. The genetic features of the genome show that the SZESBLEC201 has a unique virulence pattern compared with genetically similar strains found in the same country (China). The plasmid backbones exhibit a high degree of similarity to those of geographically distant isolates, highlighting the global spread of blaCTX-M genes and the genome plasticity of this clonal group. The coexistence of two blaCTX-M variants in the same strain increases the risk of the emergence of new blaCTX-M variants. Further studies on phage-like plasmids are necessary to provide insights into their biological activities and clinical significance.